Strain-specific differences in Neisseria gonorrhoeae associated with the phase variable gene repertoire - Jordan, P; Snyder, L; Saunders, N (BioMed Central, 2005)
Background: There are several differences associated with the behaviour of the four main experimental Neisseria gonorrhoeae strains, FA1090, FA19, MS11, and F62. Although there is data concerning the gene complements of these strains, the reasons for the behavioural differences are currently unknown. Phase variation is a mechanism that occurs commonly within the Neisseria spp. and leads to switching of genes ON and OFF. This mechanism may provide a means for strains to express different combinations of genes, and differences in the strain-specific repertoire of phase variable genes may underlie the strain differences. Results: By genome comparison of the four publicly available neisserial genomes a revised list of 64 genes was created that have the potential to be phase variable in N. gonorrhoeae, excluding the opa and pilC genes. Amplification and sequencing of the repeat-containing regions of these genes allowed determination of the presence of the potentially unstable repeats and the ON/OFF expression state of these genes. 35 of the 64 genes show differences in the composition or length of the repeats, of which 28 are likely to be associated with phase variation. Two genes were expressed differentially between strains causing disseminated infection and uncomplicated gonorrhoea. Further study of one of these in a range of clinical isolates showed this association to be due to sample size and is not maintained in a larger sample. Conclusion: The results provide us with more evidence as to which genes identified through comparative genomics are indeed phase variable. The study indicates that there are large differences between these four N. gonorrhoeae strains in terms of gene expression during in vitro growth. It does not, however, identify any clear patterns by which previously reported behavioural differences can be correlated with the phase variable gene repertoire.